Prevalensi Resistensi ARV Lini Pertama pada Pasien yang Menerima Pengobatan Haart di Klinik HIV RSUP Sanglah Bali Tahun 2014 - 2016 - Jessica Santosa; I Made Susila Utama (Universitas Udayana, 2017)
HIV is a virus that weakens the immune system. HIV can be classified into two genotypes, namely HIV-1 and HIV-2. Genotyping ofHIV-1 can be classified into three groups: group M, N, and O. Therapy for patients with positive HIV today is HAART or Highly ActiveAntiretroviral Therapy at present has much-experienced resistance to first-line. This study is an observational study with a crosssectionalstudy to determine the prevalence of resistance to first-line ARV therapy. The research was conducted from September2014 until January 2016 at the HIV clinic Sanglah Hospital. The data collection is done with a short interview and filling thequestionnaire, as well as secondary data from medical records of patients. Of the 68 samples that follow this study, 9 (13.2%) ofwhom experienced resistance and undergoing treatment with second-line antiretroviral drugs.